2017
DOI: 10.1186/s12884-017-1621-0
|View full text |Cite
|
Sign up to set email alerts
|

Women’s motivations for choosing a high risk birth setting against medical advice in the Netherlands: a qualitative analysis

Abstract: BackgroundHome births in high risk pregnancies and unassisted childbirth seem to be increasing in the Netherlands. Until now there were no qualitative data on women’s motivations for these choices in the Dutch maternity care system where integrated midwifery care and home birth are regular options in low risk pregnancies. We aimed to examine women’s motivations for birthing outside the system in order to provide medical professionals with insight and recommendations regarding their interactions with women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 36 publications
(42 reference statements)
2
48
0
Order By: Relevance
“…This is in line with other studies [18][19][20]22,33], where the pregnant woman initiated conversations about birth options that were against convention or medical recommendation. Often these plans originated in a previous traumatic experience in maternity care, where the women experienced a cascade of interventions and lack of shared decision making [18,20,24,28]. The overarching theme of 'fear' (of unnecessary intervention, loss of autonomy, provider's fear of bad outcome and legal ramifications) from our previous study on women's motivations [24] was not found to be an important factor in this current study.…”
Section: The Women Take the Lead And Filter Informationmentioning
confidence: 65%
See 2 more Smart Citations
“…This is in line with other studies [18][19][20]22,33], where the pregnant woman initiated conversations about birth options that were against convention or medical recommendation. Often these plans originated in a previous traumatic experience in maternity care, where the women experienced a cascade of interventions and lack of shared decision making [18,20,24,28]. The overarching theme of 'fear' (of unnecessary intervention, loss of autonomy, provider's fear of bad outcome and legal ramifications) from our previous study on women's motivations [24] was not found to be an important factor in this current study.…”
Section: The Women Take the Lead And Filter Informationmentioning
confidence: 65%
“…All partners were contacted through the women. The interviews with the women were the subject of previously published research by this group [24]. All partners who were asked for an interview agreed to be interviewed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Medical reasons for recommending hospital birth under supervision of an obstetrician are outlined in the Dutch national multidisciplinary list of recommendations, "the VIL. Their motivations to decline recommended care aligned with those of the women in our previous qualitative study, including disagreement about what constituted "superior knowledge," a need for autonomy and trust in the natural birth process, a conflict (elsewhere) in the negotiation of their birth plan, and a search for the type of care that they wanted.…”
Section: Resultsmentioning
confidence: 99%
“…Their motivations to decline recommended care aligned with those of the women in our previous qualitative study, including disagreement about what constituted "superior knowledge," a need for autonomy and trust in the natural birth process, a conflict (elsewhere) in the negotiation of their birth plan, and a search for the type of care that they wanted. 7 Medical reasons for recommending hospital birth under supervision of an obstetrician are outlined in the Dutch national multidisciplinary list of recommendations, "the VIL. "…”
Section: Resultsmentioning
confidence: 99%